Trends in the intellectual development of preschoolers in preschool education institutions in China - Bao Shujuan, (Scientific notes of the pedagogical department, 2023)
Problem formulation. Currently, in the People’s Republic of China, the development of the preschool educaton system has a vector aimed at the global community: teachers who train future educators, scientists, and preschool education workers themselves. Most scientists note that this process is accompanied by significant changes in preschool education. The changing preschool educational space directs its work to the development of new forms and methods of education and upbringing of preschoolers, building an individual trajectory of development of their abilities and aptitudes. Analyzing the trends of modern preschool educational institutions, researchers note that an unique situation has arisen in preschool education in recent years. The complex of various conditions (legal, regulatory, administrative, economic, socio-cultural) has formed into a certain system which allows preschool institutions to reform their activities